2022
DOI: 10.1093/nar/gkac062
|View full text |Cite|
|
Sign up to set email alerts
|

Epitranscriptomic regulation of HIV-1 full-length RNA packaging

Abstract: During retroviral replication, the full-length RNA serves both as mRNA and genomic RNA. However, the mechanisms by which the HIV-1 Gag protein selects the two RNA molecules that will be packaged into nascent virions remain poorly understood. Here, we demonstrate that deposition of N6-methyladenosine (m6A) regulates full-length RNA packaging. While m6A deposition by METTL3/METTL14 onto the full-length RNA was associated with increased Gag synthesis and reduced packaging, FTO-mediated demethylation promoted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 62 publications
5
45
0
Order By: Relevance
“…Several different laboratories have observed that the retroviral Gag proteins of HIV-1, RSV, MMTV, MLV, FIV, PFV, and MPMV undergo nuclear localization (923, 25, 26, 100103). As described in detail in this report, six previously published proteomic studies searching for binding partners of HIV-1 Gag identified many nuclear proteins (3035).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different laboratories have observed that the retroviral Gag proteins of HIV-1, RSV, MMTV, MLV, FIV, PFV, and MPMV undergo nuclear localization (923, 25, 26, 100103). As described in detail in this report, six previously published proteomic studies searching for binding partners of HIV-1 Gag identified many nuclear proteins (3035).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we identified two components of the WMM complex, CBLL1 (Cbl Pro-to-Oncogene Like 1; present in RSV and HIV-1 datasets) and WTAP (Wilms tumor 1 associated protein; RSV dataset only), which mediates m6-methyladenosine (m6A) methylation of RNAs. This RNA modification affects RNA splicing and processing, and full length HIV-1 RNA containing m6A has displayed a bias towards serving as template RNA for the translation of viral proteins, as opposed to being packaged as gRNA (103). Interaction with components of the WMM complex could simply serve to localize Gag to sites where viral RNA may exist, but it is intriguing to consider the possibility that Gag antagonizes the function of this complex to maintain a pool of genomic RNA.…”
Section: Discussionmentioning
confidence: 99%
“…In the intracellular environment, the interaction between Gag and gRNA may be regulated by many different mechanisms ( Ding et al 2021 ; Pereira-Montecinos et al 2022 ). For example, a series of reports showed that the fate of HIV-1 RNA transcripts depends on alternative transcription start sites ( Masuda et al 2015 ; Kharytonchyk et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study suggested that N 6 ‐methyladenosine deposition could play a role in regulating transcription versus packaging functions of individual HIV‐1 RNA transcripts. [ 98 ] Although this mechanism is at odds with evidence that translation and packaging are mediated by different transcripts, the proposed role for epitranscriptomic regulation of HIV‐1 RNA function is intriguing and deserves further exploration.…”
Section: Cap Sequestration Is Required For Hiv‐1 Rna Packagingmentioning
confidence: 99%